A Business Enabling Network:a case study of a high-tech network; its concepts, elements and actors - Pikka, V. (Vesa) (University of Oulu, 2007)
Abstract The phenomenon of networking has been the subject of considerable research and has made a significant contribution to business practice. In business life networks of different kinds are found as common modes of operation, and confirms the clear advantages of networks. This has increased the interest of academic research in networking. The theoretical research has extended from dyad relationships to more complicated forms, such as systems of innovation. Networking has not only been a popular research area in the field of economics, but also in the social sciences. The resulting interdisciplinary perspectives have provided new insights into the multi-faceted phenomenon of networking. This thesis is a qualitative case study. The case network is the ICTnetwork in the Oulu area in northern Finland. During the last few decades, the Oulu area has grown and established itself as one of the most important centres of wireless communication. This has been recognised worldwide and it has been labelled the “Oulu-phenomenon”. The main theoretical frameworks for this study are business and social networks theories, supplemented by innovation system and regional development theories. A network is defined in this study as A group of actors that works intentionally together to harness the long term business capabilities of the network of participants and exchange information form the business enabling network. Between the actors there can either be formal commercial relations or the relations can be informal i.e. social relations. Based on the case study, the principal contribution of this study is a novel model of networking — identified as a business enabling network — the assets of which are a goal, trust, competence, an infrastructure, and continuity. A business enabling network model is operationalized on the basis of a five-level network maturity model. These models are described in the study and provide a novel framework for the development and assessment of regional business networks. Furthermore, the study ...